2011
DOI: 10.1104/pp.111.173047
|View full text |Cite
|
Sign up to set email alerts
|

Gene Coexpression Network Alignment and Conservation of Gene Modules between Two Grass Species: Maize and Rice    

Abstract: One major objective for plant biology is the discovery of molecular subsystems underlying complex traits. The use of genetic and genomic resources combined in a systems genetics approach offers a means for approaching this goal. This study describes a maize (Zea mays) gene coexpression network built from publicly available expression arrays. The maize network consisted of 2,071 loci that were divided into 34 distinct modules that contained 1,928 enriched functional annotation terms and 35 cofunctional gene clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 63 publications
(91 reference statements)
3
120
0
Order By: Relevance
“…An important advantage of the module-based approach with respect to function prediction is that homologs are not required for a gene to receive a prediction. In agreement with a recent comparative transcriptomics study reporting conserved modules between maize and rice (Ficklin and Feltus, 2011), we observed that modules showing ultraconserved coexpression primarily cover genes that are related to energy and housekeeping functions, such as photosynthesis, ribosome biogenesis, and translation. However, the 910 modules showing significant coexpression in other angiosperms cover a broad range of biological processes and provide a valuable resource to identify new gene functions and translate biological information from model species to crops.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…An important advantage of the module-based approach with respect to function prediction is that homologs are not required for a gene to receive a prediction. In agreement with a recent comparative transcriptomics study reporting conserved modules between maize and rice (Ficklin and Feltus, 2011), we observed that modules showing ultraconserved coexpression primarily cover genes that are related to energy and housekeeping functions, such as photosynthesis, ribosome biogenesis, and translation. However, the 910 modules showing significant coexpression in other angiosperms cover a broad range of biological processes and provide a valuable resource to identify new gene functions and translate biological information from model species to crops.…”
Section: Discussionsupporting
confidence: 78%
“…These networks were built combining expression and PPI data with sequence data (Kourmpetis et al, 2011), genetic and physical interaction data (Warde-Farley et al, 2010), phylogenetic profiles and gene location (Bradford et al, 2010), and the integration of functional genomics, proteomics, and comparative genomics data sets (Lee et al, 2010). Apart from studying gene modules in one species, recent studies have applied comparisons across species to identify conserved gene coexpression in plants (Ficklin and Feltus, 2011;Movahedi et al, 2011;Mutwil et al, 2011). The analysis of coexpression networks between more distantly related species exploits the assumption that predicted gene function associations, occurring by chance within one organism, will not be conserved in a multispecies context.…”
mentioning
confidence: 99%
“…PEPC), and tetrapyrrole metabolism (Supplemental Table S4). The high connectivity of photosynthesis-related transcripts also was recently shown along the developmental gradient of the maize leaf (Pick et al, 2011) and in the large maize microarray collection analyzed by Ficklin and Feltus (2011). In our experiment, these modules enriched for chloroplast metabolism were responding mainly to the developmental stage of the maize plants.…”
Section: Weighted Correlation Network Analysismentioning
confidence: 63%
“…The weighted correlation network analysis (WGCNA) tool was developed specifically for the identification of gene coexpression networks and has so far been applied to transcriptome data from rice and maize (Ficklin et al, 2010;Ficklin and Feltus, 2011). For our experiment, we were interested in identification of modules containing genes with generally high correlation to specific metabolic processes and modules with a strong N-treatment-specific pattern.…”
Section: Weighted Correlation Network Analysismentioning
confidence: 99%
“…To evaluate relationships between multiple elements (e.g., gene or metabolite), network module analysis is a useful approach (Saito et al 2008). Network module analyses have been applied to plant gene co-expression, in which a plant gene is related to other genes based on similar expression profiles (Aoki et al 2007;Ficklin and Feltus 2011;Huber et al 2007;Marino-Ramirez et al 2009;Ogata et al 2010;Winden et al 2011). This approach allows a co-expression module, which includes coexpressed gene to be assigned to a particular biological process.…”
mentioning
confidence: 99%